The Role of Islamic Public Finance Institution in the Societal Economic Empowerment - Rahmani Timorita Yulianti (Millah: Journal of Religious Studies, 2008)
The article discusses the role of public Islamic finance institution viewed in the context of economic public endeavor. This problem emerges in public because the public Islamic finance institution in Indonesia does not take in part proportionally yet to create public prosperity in Indonesia whereas the research of the Language and Literature Center in UIN Syarif Hidayat¬ullah and Ford Foundation results that the potential of funds (Zakat, Infak, Shodaqoh) and donation of Moslems in Indonesia (IDR 19.3 billions) managed by the public Islamic finance institution can be used for people prosperity. Besides, it is supported with the big number of Moslems in Indonesia. Therefore, there are two important things to be focused on this article. First, Why has the fund in the Islamic Public Finance Institution such as ZIS and endowment in Indonesia not played optimal yet in creating social welfare? Then, how to empower the public finance institution in Indonesia?Keywords: donation, alms, Indonesia, charity